Effects of Anabolic Androgenic Steroids on Renal Morphology in Rats - Virginia A Aparicio; Daniel Camiletti-Moirón; Mohammed Tassi; Elena Nebot; Carlos de- Teresa; Pilar Aranda (Archives of Renal Diseases and Management - Peertechz Publications, 2017)
Aim: To  investigate the long-term effects of anabolic androgenic steroids (AAS)  on renal status in rats. Methods: Twenty Wistar rats were distributed into 2 groups: AAS or placebo, for 3 months.The animal received 10mg/kg body weight of Stanozonol once a week by intramuscular injection in the gluteus, or saline solution as placebo. Results: Urinary  pH  was  more  acidic  in  the  AAS  compared  to  the  placebo  group  (p<0.05).  Kidney weight was 15% higher in the AAS compared to the placebo group (p<0.001). Renal glomerular area was 12% higher in the AAS compared to the placebo group (p=0.001). Animals injected with AAS also displayed a no significant but clinically relevant ~20% higher kidney interstitial connective tissue, glomerular tufts and mesangiums. Conclusion: Overall, AAS negatively affected urinary pH and kidney morphology leading to a worse renal status. More attention should be taken to the use of AAS among populations at high risk for kidney disease.